Clerodendrumic Acid, a New Triterpenoid from Clerodendrum glabrum (Verbenaceae), and Antimicrobial Activities of Fractions and Constituents. Issue 9 (18th September 2013) - Masevhe, Ndivhaleni A.; Awouafack, Maurice D.; Ahmed, Aroke S.; McGaw, Lyndy J.; Eloff, Jacobus N.
Abstract One new triterpenoid, (3β, 11α, 19β)‐3‐(butanoyloxy)‐11‐hydroxytaraxast‐20(30)‐ene‐23, 28‐dioic acid (clerodendrumic acid; 1) was isolated from the hexane extract of the leaves of Clerodendrum glabrum var. glabrum along with heptadecanoic acid (2). The structure of the new compound was elucidated by interpretation of its NMR (1D and 2D), MS, and IR data. Combined fractions C and D from the column chromatography of the hexane extract exhibited significant antifungal activities (average MIC of 0.10 mg/ml) against Candida albicans and Cryptococcus neoformans. C. albicans was relatively resistant to clerodendrumic acid (1; MIC 125 μg/ml) and was resistant to heptadecanoic acid (2; MIC 188 μg/ml). Both compounds had low antibacterial activities against two Gram‐positive and two Gram‐negative bacteria with average MIC values of 157 and 172 μg/ml, respectively. Compounds 1 and 2 were relatively nontoxic against monkey kidney Vero cells in vitro with IC50 values of 202.6 and 108.4 μg/ml, respectively.